Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan PT Bank Central Asia KCU Kelapa Gading - Ade Muliasari; Nino Nopriandi (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to analyze the influence of the work environment and work motivation on employee performance at PT Bank Central Asia Kantor Cabang Utama Kelapa Gading. This research method uses quantitative research methods. To research the population or sample using general sampling techniques, while data collection uses research instruments and analysis methods using multiple and simple linear. The research results show that both simple and multiple work environment and work motivation have a positive and significant influence on employee performance at PT Bank Central Asia Kantor Cabang Utama Kelapa Gading.